\(\int \frac {e^{-3+e-x} (12-2 x^2) (6+2 x-x^2)}{3 (-6+x^2)} \, dx\) [4651]

   Optimal result
   Rubi [A] (verified)
   Mathematica [A] (verified)
   Maple [A] (verified)
   Fricas [A] (verification not implemented)
   Sympy [A] (verification not implemented)
   Maxima [A] (verification not implemented)
   Giac [A] (verification not implemented)
   Mupad [B] (verification not implemented)

Optimal result

Integrand size = 36, antiderivative size = 18 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=e^{-3+e-x} \left (4-\frac {2 x^2}{3}\right ) \]

[Out]

exp(ln(-2/3*x^2+4)+exp(1)-3-x)

Rubi [A] (verified)

Time = 0.05 (sec) , antiderivative size = 26, normalized size of antiderivative = 1.44, number of steps used = 10, number of rules used = 5, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.139, Rules used = {12, 21, 2227, 2225, 2207} \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=4 e^{-x+e-3}-\frac {2}{3} e^{-x+e-3} x^2 \]

[In]

Int[(E^(-3 + E - x)*(12 - 2*x^2)*(6 + 2*x - x^2))/(3*(-6 + x^2)),x]

[Out]

4*E^(-3 + E - x) - (2*E^(-3 + E - x)*x^2)/3

Rule 12

Int[(a_)*(u_), x_Symbol] :> Dist[a, Int[u, x], x] /; FreeQ[a, x] &&  !MatchQ[u, (b_)*(v_) /; FreeQ[b, x]]

Rule 21

Int[(u_.)*((a_) + (b_.)*(v_))^(m_.)*((c_) + (d_.)*(v_))^(n_.), x_Symbol] :> Dist[(b/d)^m, Int[u*(c + d*v)^(m +
 n), x], x] /; FreeQ[{a, b, c, d, n}, x] && EqQ[b*c - a*d, 0] && IntegerQ[m] && ( !IntegerQ[n] || SimplerQ[c +
 d*x, a + b*x])

Rule 2207

Int[((b_.)*(F_)^((g_.)*((e_.) + (f_.)*(x_))))^(n_.)*((c_.) + (d_.)*(x_))^(m_.), x_Symbol] :> Simp[(c + d*x)^m*
((b*F^(g*(e + f*x)))^n/(f*g*n*Log[F])), x] - Dist[d*(m/(f*g*n*Log[F])), Int[(c + d*x)^(m - 1)*(b*F^(g*(e + f*x
)))^n, x], x] /; FreeQ[{F, b, c, d, e, f, g, n}, x] && GtQ[m, 0] && IntegerQ[2*m] &&  !TrueQ[$UseGamma]

Rule 2225

Int[((F_)^((c_.)*((a_.) + (b_.)*(x_))))^(n_.), x_Symbol] :> Simp[(F^(c*(a + b*x)))^n/(b*c*n*Log[F]), x] /; Fre
eQ[{F, a, b, c, n}, x]

Rule 2227

Int[(F_)^((c_.)*(v_))*(u_), x_Symbol] :> Int[ExpandIntegrand[F^(c*ExpandToSum[v, x]), u, x], x] /; FreeQ[{F, c
}, x] && PolynomialQ[u, x] && LinearQ[v, x] &&  !TrueQ[$UseGamma]

Rubi steps \begin{align*} \text {integral}& = \frac {1}{3} \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{-6+x^2} \, dx \\ & = -\left (\frac {2}{3} \int e^{-3+e-x} \left (6+2 x-x^2\right ) \, dx\right ) \\ & = -\left (\frac {2}{3} \int \left (6 e^{-3+e-x}+2 e^{-3+e-x} x-e^{-3+e-x} x^2\right ) \, dx\right ) \\ & = \frac {2}{3} \int e^{-3+e-x} x^2 \, dx-\frac {4}{3} \int e^{-3+e-x} x \, dx-4 \int e^{-3+e-x} \, dx \\ & = 4 e^{-3+e-x}+\frac {4}{3} e^{-3+e-x} x-\frac {2}{3} e^{-3+e-x} x^2-\frac {4}{3} \int e^{-3+e-x} \, dx+\frac {4}{3} \int e^{-3+e-x} x \, dx \\ & = \frac {16}{3} e^{-3+e-x}-\frac {2}{3} e^{-3+e-x} x^2+\frac {4}{3} \int e^{-3+e-x} \, dx \\ & = 4 e^{-3+e-x}-\frac {2}{3} e^{-3+e-x} x^2 \\ \end{align*}

Mathematica [A] (verified)

Time = 0.11 (sec) , antiderivative size = 19, normalized size of antiderivative = 1.06 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=\frac {2}{3} e^{-3+e-x} \left (6-x^2\right ) \]

[In]

Integrate[(E^(-3 + E - x)*(12 - 2*x^2)*(6 + 2*x - x^2))/(3*(-6 + x^2)),x]

[Out]

(2*E^(-3 + E - x)*(6 - x^2))/3

Maple [A] (verified)

Time = 0.17 (sec) , antiderivative size = 17, normalized size of antiderivative = 0.94

method result size
gosper \({\mathrm e}^{\ln \left (-\frac {2 x^{2}}{3}+4\right )+{\mathrm e}-3-x}\) \(17\)
norman \({\mathrm e}^{\ln \left (-\frac {2 x^{2}}{3}+4\right )+{\mathrm e}-3-x}\) \(17\)
risch \(\left (-\frac {2 x^{2}}{3}+4\right ) {\mathrm e}^{{\mathrm e}-3-x}\) \(17\)
parallelrisch \({\mathrm e}^{\ln \left (-\frac {2 x^{2}}{3}+4\right )+{\mathrm e}-3-x}\) \(17\)
default \(\text {Expression too large to display}\) \(5846\)

[In]

int((-x^2+2*x+6)*exp(ln(-2/3*x^2+4)+exp(1)-3-x)/(x^2-6),x,method=_RETURNVERBOSE)

[Out]

exp(ln(-2/3*x^2+4)+exp(1)-3-x)

Fricas [A] (verification not implemented)

none

Time = 0.22 (sec) , antiderivative size = 16, normalized size of antiderivative = 0.89 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=e^{\left (-x + e + \log \left (-\frac {2}{3} \, x^{2} + 4\right ) - 3\right )} \]

[In]

integrate((-x^2+2*x+6)*exp(log(-2/3*x^2+4)+exp(1)-3-x)/(x^2-6),x, algorithm="fricas")

[Out]

e^(-x + e + log(-2/3*x^2 + 4) - 3)

Sympy [A] (verification not implemented)

Time = 0.06 (sec) , antiderivative size = 15, normalized size of antiderivative = 0.83 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=\frac {\left (12 - 2 x^{2}\right ) e^{- x - 3 + e}}{3} \]

[In]

integrate((-x**2+2*x+6)*exp(ln(-2/3*x**2+4)+exp(1)-3-x)/(x**2-6),x)

[Out]

(12 - 2*x**2)*exp(-x - 3 + E)/3

Maxima [A] (verification not implemented)

none

Time = 0.24 (sec) , antiderivative size = 21, normalized size of antiderivative = 1.17 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=-\frac {2}{3} \, {\left (x^{2} e^{e} - 6 \, e^{e}\right )} e^{\left (-x - 3\right )} \]

[In]

integrate((-x^2+2*x+6)*exp(log(-2/3*x^2+4)+exp(1)-3-x)/(x^2-6),x, algorithm="maxima")

[Out]

-2/3*(x^2*e^e - 6*e^e)*e^(-x - 3)

Giac [A] (verification not implemented)

none

Time = 0.27 (sec) , antiderivative size = 24, normalized size of antiderivative = 1.33 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=-\frac {2}{3} \, x^{2} e^{\left (-x + e - 3\right )} + 4 \, e^{\left (-x + e - 3\right )} \]

[In]

integrate((-x^2+2*x+6)*exp(log(-2/3*x^2+4)+exp(1)-3-x)/(x^2-6),x, algorithm="giac")

[Out]

-2/3*x^2*e^(-x + e - 3) + 4*e^(-x + e - 3)

Mupad [B] (verification not implemented)

Time = 0.17 (sec) , antiderivative size = 16, normalized size of antiderivative = 0.89 \[ \int \frac {e^{-3+e-x} \left (12-2 x^2\right ) \left (6+2 x-x^2\right )}{3 \left (-6+x^2\right )} \, dx=-\frac {2\,{\mathrm {e}}^{-x}\,{\mathrm {e}}^{-3}\,{\mathrm {e}}^{\mathrm {e}}\,\left (x^2-6\right )}{3} \]

[In]

int((exp(log(4 - (2*x^2)/3) - x + exp(1) - 3)*(2*x - x^2 + 6))/(x^2 - 6),x)

[Out]

-(2*exp(-x)*exp(-3)*exp(exp(1))*(x^2 - 6))/3